ANALISIS FAKTOR·FAKTOR YANG lWEMPENGARUHI PENDAPATAN USAHA KELUARGA TRANSMIGRAN PETERNAK SAPI DI KECAMATAN PAIWENANG KABUPATEN MERANGIN - Latifa Siswati; Ali Mutahar (Jurnal Peternakan, 2005)
This research a~s to know the income level of integrated farming system on transmigrant family. The research was ~arned ~ut ~t 8 -22 December 1999 in Bukit Tungkul, Tamb.mg Emas and !!,antak Seribu, Pamen~g, Mer~gm,Jambl, ~smg survey methode. The sample was collected using Simple Random Sampling and Purpos~ve Samplmg. ~he vanable of the research are animal scale, holticulture area, farm periode, stay periode in. transmlgrant area, sharmg percentage, family labour and holticulture type. The result indicated that the income ofintegrated farming system are about Rp 4.909.573.34/ year.